Quantitative Trait Loci Associated with Drought Tolerance in Brachypodium distachyon - Jiang, Yiwei; Wang, Xicheng; Yu, Xiaoqing; Zhao, Xiongwei; Luo, Na; Pei, Zhongyou; Liu, Huifen; Garvin, David F. (Frontiers in Plant Science, 2017)
The temperate wild grass Brachypodium distachyon (Brachypodium) serves as model system for studying turf and forage grasses. Brachypodium collections show diverse responses to drought stress, but little is known about the genetic mechanisms of drought tolerance of this species. The objective of this study was to identify quantitative trait loci (QTLs) associated with drought tolerance traits in Brachypodium. We assessed leaf fresh weight (LFW), leaf dry weight (LDW), leaf water content (LWC), leaf wilting (WT), and chlorophyll fluorescence (Fv/Fm) under well-watered and drought conditions on a recombinant inbred line (RIL) population from two parents (Bd3-1 and Bd1-1) known to differ in their drought adaptation. A linkage map of the RIL population was constructed using 467 single nucleotide polymorphism (SNP) markers obtained from genotyping-by-sequencing. The Bd3-1/Bd1-1 map spanned 1618 cM and had an average distance of 3.5 cM between adjacent single nucleotide polymorphisms (SNPs). Twenty-six QTLs were identified in chromosome 1, 2, and 3 in two experiments, with 14 of the QTLs under well-watered conditions and 12 QTLs under drought stress. In Experiment 1, a QTL located on chromosome 2 with a peak at 182 cM appeared to simultaneously control WT, LWC, and Fv/Fm under drought stress, accounting for 11% to 18.7% of the phenotypic variation. Allelic diversity of candidate genes DREM2B, MYB, and SPK, which reside in one multi-QTL region, may play a role in the natural variation in whole plant drought tolerance in Brachypodium. Co-localization of QTLs for multiple drought-related traits suggest that the gene(s) involved are important regulators of drought tolerance in Brachypodium.